La necesidad de la memoria y el estudio histórico. El caso de la emisora Radio Cádiz y la resistencia al golpe de Estado el 18 de julio de 1936 - José Luis Gutiérrez Molina (Cahiers de Civilisation Espagnole Contemporaine)
Spanish Decades of dictatorship and many others of democratic silence have caused that many of the events that took place during the coup d’état of July 1936 and those that followed, remain more in the field of propaganda and lies than in the historical account. This need for «truth» is one of the pillars of the so-called movement for historical memory. An especially relevant case to understand what happened in the Andalusian city of Cádiz is the reading of a note from the Civil Governor by the local radio station in which the resistance was called. The coup plotters presented it as an evidence of the vesanía of the authorities and the chaos that occurred in the city after the beginning of the coup and the government and citizen response. This version has remained in the city as the historical truth. This text dismantles what has never ceased to be an element of propaganda, in the light of a documentation found in military archives.